[Spichlerze przy ul. Chmielnej] [aut. odb. Karol Nowaliński]. - Nowaliński, Karol (1935- ). (Karol Nowaliński, 1986)
Przedstawia spichlerze przy ul. Chmielnej (Hopfengasse), widok od ul. Szafarnia (Schäferei), ok. 1910 r.